Influence Of Work Discipline And Work Motivation On Employee Productivity - Yudiyanto Joko Purnomo; Rinaldy Jayadiningrat (Universitas 17 Agustus 1945 Semarang, 2023)
This study aims to analyze the factors of work discipline and work motivation factors that have an influence on employee productivity in the production unit of PT Ateja Grace Texindo. This study used descriptive analysis using Google Forms as a data collection method for 30 employee respondents at the production unit of PT Ateja Grace Texindo. The sampling method in this study used non-probability sampling. Then the data was processed and analyzed using the IBM SPSS Statistic 22 software application. This study found that work motivation factors have an influence on employee productivity at PT Ateja Grace Texindo in the production unit section. However, the work discipline factor has no effect on employee productivity at PT Ateja Grace Texindo in the production unit section.